Perspektif Antropologi dan Teori Komunikasi: Penelusuran Teori-teori Komunikasi dari Disiplin Antropologi - Sri Rejeki, MC Ninik (FISIP Universitas Atma Jaya Yogyakarta, 2010)
Abstract : It is important to learn the perspectives derived in communication theories in order to well understand the focuses and characteristic of those theories. There are several perspectives and one of them is derived form Anthroplogy. In this sense, communication is considered as having holistic character and concern in interpretive activities. In this regards, communication is contextualized by culture. Therefore as well culture is unique, communication is also unique. There are several kinds of contribution of Anthropology in the development of communication theories which can be traced. First, structural linguistic as the branch study of linguistic anthropology contributes in semiotics studies. As well, sociolinguistic contributes to understand the relationsip between social reality and culture. Second, in the area of historical archeology, the contrubition of Anthropology is represented in the frame of knowledge on unwritten communication activities. Third, the contribution of ethnology in innovation and diffussion theory as well as ethnography in the emergence of experience and interpretation theories also represent the contribution of Anhtropology. Similary, it can be traced the contribution of Anthropology through the contribution of ethnohistory in explaining the modes of communication of certain community.